Balancing excellence and diversity in higher education? The role of the Chinese first-level discipline evaluation scheme. Issue 2 (3rd July 2019) - Dong, Xilu; Maassen, Peter; Stensaker, Bjørn
ABSTRACT: Balancing excellence and diversity effectively in the higher education sector is one of the most challenging tasks for national governments. While a number of countries around the world have initiated university excellence schemes, it is more difficult to identify policy initiatives that also take into account how institutional diversity is to be enhanced simultaneously. By an in-depth analysis of the voluntary, and later mandatory, first-level discipline evaluation scheme in China from 2003 to 2016, the article discusses possible long-term impacts of this scheme both regarding excellence and diversity in the higher education landscape in the country. In conclusion, it is argued that decentralized decision-making within a centralized evaluation scheme is an interesting governance approach for trying to balance excellence and diversity in higher education. However, institutional diversity is not necessarily positively correlated to disciplinary diversity.